2015
DOI: 10.1038/ncb3240
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical NF-κB signalling and ETS1/2 cooperatively drive C250T mutant TERT promoter activation

Abstract: Transcriptional reactivation of TERT, the catalytic subunit of telomerase, is necessary for cancer progression in about 90% of human cancers. The recent discovery of two prevalent somatic mutations—C250T and C228T—in the TERT promoter in various cancers has provided insight into a plausible mechanism of TERT reactivation. Although the two hotspot mutations create a similar binding motif for E-twenty-six (ETS) transcription factors, we show that they are functionally distinct, in that the C250T unlike the C228T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
199
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(211 citation statements)
references
References 69 publications
11
199
1
Order By: Relevance
“…We were unable to test whether or not the observed differences in the extent of MGMT methylation actually reflect differences in tumor purity because of the required quantile normalization between the C228 and C250 qAS-PCR assays. Similarly, several studies have shown differences in TERT mRNA expression levels between the two hotspot mutations with higher expression in C250T-mutated GBM samples (23,40). We observed the same trend in our data, but we instead propose attributing this finding to collinearity with tumor purity.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…We were unable to test whether or not the observed differences in the extent of MGMT methylation actually reflect differences in tumor purity because of the required quantile normalization between the C228 and C250 qAS-PCR assays. Similarly, several studies have shown differences in TERT mRNA expression levels between the two hotspot mutations with higher expression in C250T-mutated GBM samples (23,40). We observed the same trend in our data, but we instead propose attributing this finding to collinearity with tumor purity.…”
Section: Discussioncontrasting
confidence: 50%
“…This is perhaps reasonable as both hotspot mutations are known to generate an identical Ets/TCF transcription factorbinding motif (37)(38)(39). Very recently, however, functional differences between the C228T and C250T mutations with respect to NF-kB pathway activation has been reported (40). Profound biological differences, for example, in tumor purity, between tumors carrying the C228T versus the C250T point mutation are thus likely.…”
Section: Discussionmentioning
confidence: 99%
“…40 The 2146C>T mutation in the TERT promoter, on the other hand, has been shown to be driven by noncanonical NF-kB signaling. 41 Incidentally, in melanoma both 2124C>T and 2146C>T mutations occur at almost similar frequencies; in all other malignancies the former mutation is overwhelmingly predominant. 39 Telomerase activity in human tissues is restricted due to transcriptional silencing of TERT following differentiation.…”
Section: Cancer Genetics and Epigeneticsmentioning
confidence: 99%
“…Another study in glioblastoma, reported that although the −124C > T and −146C > T mutations create similar binding motif sequences, they are distinct functionally (Li et al 2015b). The −146C > T creates a specific binding site for p52 being driven by non-canonical NF-κB signalling pathway (Li et al 2015b).…”
Section: Functional Effects Of Tert Promoter Mutations In Tumours Andmentioning
confidence: 99%
“…The −146C > T creates a specific binding site for p52 being driven by non-canonical NF-κB signalling pathway (Li et al 2015b). Li and coworkers also elucidate that the binding of ETS alone is ineffective in the activation of TERT transcription in the −146C > T mutation (Li et al 2015b).…”
Section: Functional Effects Of Tert Promoter Mutations In Tumours Andmentioning
confidence: 99%